Genotoxic effect of two commonly used food dyes metanil yellow and carmoisine using Allium cepa L. as indicator - Ishfaq Shafi Khan; Md. Niamat Ali; Rabia Hamid; Showkat Ahmad Ganie (Toxicology Reports, 2020)
Food dyes are important component of food in this fast life. Metanil yellow and carmoisine are two azo dyes which are being used at an alarming rate for increasing visual appearance and consumer validity of food. There is a lot of controversy regarding the genotoxicity of these two dyes. In the present study genotoxicity of two food dyes metanil yellow and carmoisine was evaluated using Allium cepa as indicator. The effect of these two azo dyes was determined at concentration of 0.25 %, 0.50 %, 0.75 % and 1.0 % for 24 h and 48 h of exposure period using root meristematic cells of Allium cepa. Some genotoxicity parameters like mitotic indices and chromosomal aberrations were studied. It was found that both metanil yellow and carmoisine caused a significant reduction in mitotic index and also produce different kinds of chromosomal aberrations mostly at higher concentration and longer exposure period. The different kinds of aberrations that were observed in meristematic cells after treatment with both metanil yellow and carmoisine are disorientation at metaphase, metaphase stickiness, anaphase stickiness, anaphase bridge, c-mitosis and chromosome breaks. The genotoxicity of carmoisine was found very high as compared to metanil yellow at all concentrations and exposure periods. Thus it was concluded from the present study that carmoisine and metanil yellow have genotoxic activities and should be taken in very control and limited doses.